O041 Pre-bedtime device use disrupts sleep in early adolescents: differential effects depending on device type and media content. (9th November 2022) - Lu, S; Phillips, A; Hand, A; Chachos, E; Carskadon, M; Lockley, S; Wiley, J; Bei, B; Klerman, E; Rajaratnam, S; Stone, J
Abstract: Using light-emitting devices before bed is a modifiable behaviour that may affect adolescent sleep. We investigated the daily associations between device use before bed and sleep-wake timing, duration, and quality in early adolescence. Participants were 168 Year 7 students (M±SD=12.82±0.42 years, 56% females) in Australia. Sleep-wake timing, sleep quality, and device use in the hour before bed (device type and media content) were measured using daily diaries for two weeks during school term. Linear mixed models were used to examine the association between device use in the hour before bed and sleep outcomes. Nearly all (99%) participants used devices before bed on at least one night, with 58% using devices before bed every night during the two-week monitoring period. Using devices to access social media predicted later reported sleep onset, longer sleep onset latency, and shorter sleep duration (all p<.05). Similarly, playing games, watching videos, or using a game console all predicted later sleep onset that night (all p<.05), and watching television predicted more wake after sleep onset (p<.01). In contrast, using devices for homework predicted earlier sleep onset (p<.05), while reading on devices predicted better sleep quality (p<.05). Our findings indicate that the type of device, and what they are used for before bed, may have different effects on sleep, potentially due to differences in light exposure levels and/or their impact on arousal systems. These findings may help inform existing guidelines for healthy pre-bedtime device use in adolescents.